Analysis of Employee Competency, Monitoring, Motivation, and Performance in the Warriors Kulon District, Mojokerto - rulianto elvin; Endang Suswanti; M. Jamal Abdul Nasir (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Purpose - This study aims to analyze the direct effect of employee competence andmonitoring on motivation and performance, the effect of motivation on performance,and to analyze the indirect effect between employee competence and monitoring onperformance through motivation as a mediating variable.Design/methodology/approach - This study used a research instrument in the formof a questionnaire with a path analysis test and was processed using the SPSS Ver22 program.Findings - The results of the study show that: employee competence and monitoringhave a significant effect on employee motivation, employee competence has nosignificant effect on performance, monitoring and motivation have a significanteffect on performance, competence has no significant effect on performance throughmotivation, and monitoring has a significant effect on performance throughmotivation.